Psychostimulant Effect of the Synthetic Cannabinoid JWH-018 and AKB48: Behavioral, Neurochemical, and Dopamine Transporter Scan Imaging Studies in Mice - Ossato, Andrea; Uccelli, Licia; Bilel, Sabrine; Canazza, Isabella; Di Domenico, Giovanni; Pasquali, Micol; Pupillo, Gaia; De Luca, Maria Antonietta; Boschi, Alessandra; Vincenzi, Fabrizio; Rimondo, Claudia; Beggiato, Sarah; et al. (Frontiers in Psychiatry, 2017)
JWH-018 and AKB48 are two synthetic cannabinoids (SCBs) belonging to different structural classes and illegally marketed as incense, herbal preparations, or chemical supply for theirs psychoactive cannabis-like effects. Clinical reports from emergency room reported psychomotor agitation as one of the most frequent effects in people assuming SCBs. This study aimed to investigate the psychostimulant properties of JWH-018 and AKB48 in male CD-1 mice and to compare their behavioral and biochemical effects with those caused by cocaine and amphetamine. In vivo studies showed that JWH-018 and AKB48, as cocaine and amphetamine, facilitated spontaneous locomotion in mice. These effects were prevented by CB1 receptor blockade and dopamine (DA) D1/5 and D2/3 receptors inhibition. SPECT-CT studies on dopamine transporter (DAT) revealed that, as cocaine and amphetamine, JWH-018 and AKB48 decreased the [123I]-FP-CIT binding in the mouse striatum. Conversely, in vitro competition binding studies revealed that, unlike cocaine and amphetamine, JWH-018 and AKB48 did not bind to mouse or human DAT. Moreover, microdialysis studies showed that the systemic administration of JWH-018, AKB48, cocaine, and amphetamine stimulated DA release in the nucleus accumbens (NAc) shell of freely moving mice. Finally, unlike amphetamine and cocaine, JWH-018 and AKB48 did not induce any changes on spontaneous [3H]-DA efflux from murine striatal synaptosomes. The present results suggest that SCBs facilitate striatal DA release possibly with different mechanisms than cocaine and amphetamine. Furthermore, they demonstrate, for the first time, that JWH-018 and AKB48 induce a psychostimulant effect in mice possibly by increasing NAc DA release. These data, according to clinical reports, outline the potential psychostimulant action of SCBs highlighting their possible danger to human health.